2007
DOI: 10.1088/0022-3727/40/12/021
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of ZnSxSe1−xfilms deposited by close-spaced evaporation

Abstract: Polycrystalline thin films of ZnSxSe1−x with x = 0, 0.25, 0.5, 0.75 and 1.0 have been synthesized using close-spaced evaporation. The films were deposited onto glass substrates at different substrate temperatures in the range 200–400 °C. The grown films were characterized using XRD, AFM, EDAX and UV–Vis–NIR spectrophotometer to determine the microstructural properties, composition and optical behaviour. All the ZnSxSe1−x films deposited between 275 and 300 °C were crystallized in cubic structure with a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Until now, a wide range of characterization studies of the ZnSSe thin films have been reported, including structural, electrical and optical properties variations in dependence of the S/Se ratio. 2,5,7,[10][11][12][13][14][15][16] Raman spectroscopy as such has been extensively used for investigating the lattice vibration dynamics in these systems. 12,14,17,18 Raman scattering is a powerful non-destructive method which can provide useful information on the structure, morphology and chemical composition of semiconductor materials, as well as on the photon-electron and electron-phonon interactions occurring in these materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, a wide range of characterization studies of the ZnSSe thin films have been reported, including structural, electrical and optical properties variations in dependence of the S/Se ratio. 2,5,7,[10][11][12][13][14][15][16] Raman spectroscopy as such has been extensively used for investigating the lattice vibration dynamics in these systems. 12,14,17,18 Raman scattering is a powerful non-destructive method which can provide useful information on the structure, morphology and chemical composition of semiconductor materials, as well as on the photon-electron and electron-phonon interactions occurring in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Polycrystalline ZnSSe compounds are excellent candidates for window and/or buffer layers in thin film heterojunction solar cells and promising alternatives to the presently explored materials such as CdS, which contain toxic Cd. 5,6 Additionally, because of its low absorption at infrared wavelength and exciton binding energy, ZnSSe is considered as a future material in the production of biomedical labels, output couplers, lenses, and optically controlled switches. Changing the ratio of S to Se of ZnSSe compounds leads to tuning of the electron affinity and electrical properties which greatly enhances the blue response of the material.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk, single crystal and polycrystalline thin films have been growth and characterized for these applications (Kontos, G.et al,2003;Jung, J. H., et al,2007;Li F., et al,2008;Zhu X. L., et al,2007). Polycrystalline thin films of ZnS1-xSex have been reported for different optoelectronic applications such as blue lasers and blue laser diodes (Patil D. et al,2004), heterojunction nontoxic solar cells (Subbaiah Y., et al,2007;Subbaiah, Y., et al,2008) etc. Now a days, growth and characterization of nanostructure ZnS1-xSex composite thin films have wide scope for optoelectronic device applications.…”
Section: Introductionmentioning
confidence: 99%